Land use changes into the Palestinian central mountains: Nablus Municipality, a case study - Ghazal, Sana Khalid Hasan (Africana Studia, 2022)
Over the past six decades, the villages that were annexed to Nablus Municipality Boundaries have lost their agricultural, pastures and plains lands which were estimated by 18,000 dunum. This study examines the land use changes of villages’ annexed land to Nablus Municipality Boundaries, especially how the land use of 15 villages annexed have changed since 1963-2016. The study concludes that the changes in land-uses occurred from agricultural, pastures and plains to industrial, residential and service uses. In 1963 the agricultural land had an area of 3,000 dunum, the plains of 6,000 dunum and the pastures of 9,000 dunum. Almost all these areas were converted to non-agricultural land-uses. Keywords: Land use, land annexation, Nablus Municipality Boundaries.